2017
DOI: 10.1093/aobpla/plx059
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of chasmogamy and cleistogamy, a mixed-mating strategy in an endangered perennial

Abstract: Our research explores patterns of mixed-mating in the endemic, federally listed Polygala lewtonii. This perennial herb has open-pollinated chasmogamous flowers and self-pollinated cleistogamous flowers on both above- and below-ground stems. Data collected from 2008 - 2012 shows temporal separation of chasmogamy (January to May) and cleistogamy (June to February) with little overlap. A quarter of plants flowered all three flower morphs at least once during their lifespan while slightly less than half produced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Although not explicitly testing for EDID, a similar result was observed by Koontz et al. (), who found that Polygala lewtonii Small [Polygalaceae] invests more in the production of open flowers, whereas most of the individuals surviving to reproductive maturity issued from closed flowers. In that species too, it is likely that seed‐set variation impacts the parent plant's fitness more than differences in offspring performance.…”
Section: Discussionsupporting
confidence: 70%
“…Although not explicitly testing for EDID, a similar result was observed by Koontz et al. (), who found that Polygala lewtonii Small [Polygalaceae] invests more in the production of open flowers, whereas most of the individuals surviving to reproductive maturity issued from closed flowers. In that species too, it is likely that seed‐set variation impacts the parent plant's fitness more than differences in offspring performance.…”
Section: Discussionsupporting
confidence: 70%
“…Some plant species that bear 2 or more heteromorphic flowers also bear heteromorphic fruits (seeds). Amphicarpy is a phenomenon in which a plant produces both aerial and subterranean flowers and simultaneously bears both aerial and subterranean fruits (seeds) on aerial-and subterranean-stems, respectively (Cheplick, 1987;Koontz et al, 2017;Schnee and Waller, 1986). This phenomenon is observed in at least 67 herbaceous species (31 in Fabaceae) in 39 genera and 13 families of angiosperms, as reported by Zhang et al (Zhang et al, 2020a).…”
Section: Introductionmentioning
confidence: 81%
“…Mixed-mating in amphicarpic species provides a fitness advantage through production of genetically diverse progeny via CH flowers, while preserving locally adapted alleles via CL flowers (Koontz et al, 2017). More biomass (energy) is required to produce CH than CL flowers, and CL flowers may produce more seeds than CH flowers (Schoen & Lloyd, 1984;Oakley, Moriuchi, & Winn, 2007;Winn & Moriuchi, 2009;Koontz et al, 2017). However, CL flowers increase the susceptibility of a population to genetic drift and inbreeding depression if deleterious alleles cannot be purged (Zeide, 1978;Oakley et al, 2007; see papers on purging by Crnokrak &Barrett, 2002 andDart &Eckert, 2013).…”
Section: Cleistogamy and Breeding Systemmentioning
confidence: 99%
“…In the amphicarpic perennial herbs Polygala lewtonii (Swift et al ., 2016) and Trifolium polymorphum (Real et al ., 2007), self‐fertilization ranged from 80 to 93% and 60%, respectively. Mixed‐mating in amphicarpic species provides a fitness advantage through production of genetically diverse progeny via CH flowers, while preserving locally adapted alleles via CL flowers (Koontz et al ., 2017). More biomass (energy) is required to produce CH than CL flowers, and CL flowers may produce more seeds than CH flowers (Schoen & Lloyd, 1984; Oakley, Moriuchi, & Winn, 2007; Winn & Moriuchi, 2009; Koontz et al ., 2017).…”
Section: Cleistogamy and Breeding Systemmentioning
confidence: 99%
See 1 more Smart Citation